2007
DOI: 10.1002/pd.1797
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of Fryns syndrome associated with a microdeletion at 8p23.1

Abstract: A 33-year-old, unmarried, primigravid woman was referred to the hospital at 24 weeks' gestation because of abnormal sonographic findings. The mother and the father were not consanguineous and healthy. There was no family history of congenital malformations. A cytogenetic study performed on the amniotic fluid cells revealed a karyotype of 46,XX at the 850band stage. Level II ultrasound at 24 weeks' gestation revealed polyhydramnios, macrocephaly with a head circumference of 24.1 cm (>95th centile), ventriculome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Chromosome 8p contains many copy number variant regions whose potential contribution to the development of birth defects has not been adequately studied. Recently, Chen et al 2007 described a patient with a Fryns‐like phenotype including CDH, macrocephaly, brachytelephalangy, nail hypoplasia, short webbed neck with redundant posterior nuchal skin, coarse face, flat and broad nasal bridge, hypertelorism, macrostomia, microretrognathia, and low‐set ears. The patient's phenotype was attributed to a de novo 0.7 Mb deletion within 8p23.1 [Chen et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome 8p contains many copy number variant regions whose potential contribution to the development of birth defects has not been adequately studied. Recently, Chen et al 2007 described a patient with a Fryns‐like phenotype including CDH, macrocephaly, brachytelephalangy, nail hypoplasia, short webbed neck with redundant posterior nuchal skin, coarse face, flat and broad nasal bridge, hypertelorism, macrostomia, microretrognathia, and low‐set ears. The patient's phenotype was attributed to a de novo 0.7 Mb deletion within 8p23.1 [Chen et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al 2007 described a patient with a Fryns‐like phenotype including CDH, macrocephaly, brachytelephalangy, nail hypoplasia, short webbed neck with redundant posterior nuchal skin, coarse face, flat and broad nasal bridge, hypertelorism, macrostomia, microretrognathia, and low‐set ears. The patient's phenotype was attributed to a de novo 0.7 Mb deletion within 8p23.1 [Chen et al, 2007]. However, this deletion lies entirely within a known copy number variant region making it difficult to determine if this deletion is causal.…”
Section: Discussionmentioning
confidence: 99%
“…S. Giglio reported that haploinsufficiency of the region between WI-8372 (6.36–6.57 Mb) and D8S1825 (8.86–9.06 Mb) was associated with congenital heart defects using short-tandem repeat (STR) analysis [23], which suggested that the REPD may be related to CHD. However, Chen found that the microdeletion (chr8∶7227000–7916187) was insufficient to induce heart defects [24].…”
Section: Discussionmentioning
confidence: 99%
“…More telomeric deletions, which do not overlap the hotspot region, may be unrelated to the “classical” del(8)(p23.1) syndrome. Chen et al [2007] reported an infant with CDH and additional anomalies, clinically diagnosed as having Fryns syndrome. Standard chromosome analysis was normal (46,XX) but focused aCGH revealed a de novo 0.7 Mb deletion in sub‐band 8p23.1, which extended from base pairs 7,227,000 to 7,916,187 (NCBI36/hg18).…”
Section: Discussionmentioning
confidence: 99%